KAJIAN EKONOMI WILAYAH KABUPATEN KUDUS DALAM RANGKA PENGEMBANGAN PERBANKAN (STUDI KASUS PADA SEKTOR BPR KONVENSIONAL) - Maskur, Ali; Waluyo, Purwanto; Marlien, R.A (Proceeding Fakultas Ekonomi, 2012)
The aim of his study is to examine the economy potential of Kabupaten Kudus for micro banking investment change bu using the historical data for periode of 2005-2009, and by applying descriptive analysis and trend analysis. Factor that analysis is ; demografy, gross regional domestic product, income per kapita and banking competitions. The result found the regional economic of Kabupaten Kudus growth for periode 2005 â 2009 and beyond. It also found that the market competitions of banking is low which is able to stimulate a policy is needed to motivate all parties to make invesment in this area. Finally, it is recommended that to increase micro banking investment of Kabupaten Kudus.Keyword : The condition of regional economic, the market competition of banking, bussines feasibility, captive market.